Production Of Mannan-Degrading Enzymes By Aspergillus Niger In Solid State And Submerged Fermentation For Hydrolysis Of Palm Kernel Cake - Ong, Lisa Gaik Ai (2006)
The production of mannan degrading enzymes under solid substrate fermentation and liquid fermentation by Aspergillus niger FTCC 5003 were carried using palm kernel cake (PKC) as the sole carbon source. The crude enzymes produced were then used in the enzymatic hydrolysis of PKC. In the preliminary study, it was observed that mannanase was the highest enzyme activity produced. Other enzymes produced were, amylase, xylanase, polygalacturonase and cellulases. Types of inoculum and extraction temperature play an important role in the production of mannanase under solid substrate fermentation (SSF). The optimum parameters for the mannanase production in submerged fermentation (SmF) under shake flask condition were 1×104 spores/mL, with 2% (w/v) of PKC incubated at 35ºC, and agitated at 200 rpm. While the optimum parameters for mannanase production in SSF were 1×106 spores/mL, with 50% (v/w) of initial moisture content, 2% of nitrogen in urea and incubated at 30ºC. Mannanase produced under optimum condition was 104 U/mL (SmF) and 1705 U/g PKC (SSF). Mannanase obtained from SSF was more heat stable as compared to those obtained from SmF. Both types of mannanase had the same optimum pH, which was pH 7 and both had two different optimum temperatures, which were 30°C and 50°C for SmF; and 35°C and 55°C for SSF. For the enzymatic hydrolysis of PKC, the optimum condition for the hydrolysis was 10% of PKC, 100 U/mL enzyme concentration, at 45°C and pH 6.5 when mannanase obtained from SmF was used. On the other hand, when mannanase from SSF was used the optimum condition was obtained at 45°C, pH 7.5 with 10% PKC and 50 U/mL enzyme concentration.